2019
DOI: 10.15666/aeer/1705_1025310266
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks (A New Statistical Approach) Method in Length-Weight Relationships of Alburnus Mossulensis in Murat River (Palu-Elaziğ) Turkey

Abstract: Artificial Neural Networks (ANNs) is a reliable and alternative method used specially in the growth characteristics of some fish species. The purpose of this work was to compare with length-weight relationships and Artificial Neural Networks, the length-weight relation of 415 (232 female and 183 male) Alburnus mossulensis captured from Murat River between January 2018 and December 2018. The total length and the weight of the fish changed between 7.2-19.9 cm (12.81±0.095) and 3.24-40.6 g (13.51±0.30) respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…It has been observed that there is a high affinity between the measured and predicted data and the values obtained with ANN are closer to the real values (Ozcan and Serdar, 2018). Also Ozcan (2019) pointed out that ANN can be used as an alternative method for estimation of population. In the present study, SVR performance metric results are 0.996 and 0.992 values both for the lengthweight of male and female individuals, with 0.996 and 0.995 values and for the length-meat yield of males and females are closer to the values of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that there is a high affinity between the measured and predicted data and the values obtained with ANN are closer to the real values (Ozcan and Serdar, 2018). Also Ozcan (2019) pointed out that ANN can be used as an alternative method for estimation of population. In the present study, SVR performance metric results are 0.996 and 0.992 values both for the lengthweight of male and female individuals, with 0.996 and 0.995 values and for the length-meat yield of males and females are closer to the values of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that there is a high affinity between the measured and predicted data and the values obtained with ANN are closer to the real values [39]. Also Ozcan [40] pointed out that ANN can be used as an alternative method for estimation of population. In the present study, SVR performance metric results are 0.996 and 0.992 values both for the length-weight of male and female individuals, with 0.996 and 0.995 values and for the length-meat yield of males and females are closer to the values of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies on predictive modeling using neural networks for the growth of aquatic organisms, specifically focusing on fish (Benzer and Benzer 2016, Benzer and Benzer 2017, Özcan and Serdar 2018, Özcan and Serdar 2019, Özcan 2019, Benzer and Benzer 2020, Benzer and Benzer 2023b, Akkan et al 2024) and crayfish (Türeli Bilen et al 2011, Benzer et al 2015, Benzer and Benzer 2018, Benzer and Benzer 2022.…”
Section: Introductionmentioning
confidence: 99%